Bilaspur Marches On! - Planning Commission (Planning Commission)
The State of Bilaspur Kehloor is a beautiful compact tract of land of various and luxurious growth. Embracing an area of 450 square miles, it is embossed in the outer hills of the Himalayas bordering on the plains. Its hills and valleys, streams and rivulets make it into a picturesque abode of a hundred and ten thousand souls. The Satluj River, in its tortuous course of well over fifty miles, divides it into two slightly unequal parts, which with all their peculiarities form one harmonious whole, unanimous in thought and in deed. This river with its tributaries forming the main drainage system of this territory has not been an unmixed liability. On the other hand, along with the proverbial seven hills of the State, it for centuries formed a worthy rampart of this historical land. Geographically therefore, the State is enviably situated. Perhaps nature in its own way, wanted it to form a unique link between the hills and the plains.
A 10 Year Plan